1978
DOI: 10.1901/jeab.1978.30-281
|View full text |Cite
|
Sign up to set email alerts
|

Warmup in Free‐operant Avoidance as a Function of the Response‐shock = Shock‐shock Interval

Abstract: Warmup effects, the repeated within-session transitions from ineffective to effective avoidance, were examined with rats on free-operant shock-delay procedures. The shock-shock and response-shock intervals were kept equal as they were varied. As measured by both response rates and shock rates, the magnitude of within-session change in performance was inversely related to the size of the manipulated intervals. The duration of warmup tended to decrease as the intervals were increased. This finding, that increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

1981
1981
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…This, too, is consistent with results in the shock-avoidance realm where experienced subjects avoid a high percentage of scheduled shocks. One common effect reported with shock-avoidance but absent in the present study is the transient early session decrement in responding-the socalled ''warm-up effect'' (Hineline, 1978). We examined within-session responding but found no evidence of changes in TO rate across the session.…”
Section: Discussioncontrasting
confidence: 53%
“…This, too, is consistent with results in the shock-avoidance realm where experienced subjects avoid a high percentage of scheduled shocks. One common effect reported with shock-avoidance but absent in the present study is the transient early session decrement in responding-the socalled ''warm-up effect'' (Hineline, 1978). We examined within-session responding but found no evidence of changes in TO rate across the session.…”
Section: Discussioncontrasting
confidence: 53%
“…Some studies have found that changing inten-sity alters warm-up (e.g., Leander, 1973); others have found that it does not (e.g., Hoffman et al, 1961;Powell, 1970b). Shock frequency also exerts little control over the size of warmup (e.g., Hineline, 1978a) but it does alter performance later in the session.…”
Section: Aversive Stimuli Avoidancementioning
confidence: 99%
“…Except for warm-up for avoidance (e.g., Hineline, 1978aHineline, , 1978b, neither priming nor warm-up has been studied in systematic detail. However, what is known suggests that neither procedure is related to the present functions.…”
Section: Subje-ctmentioning
confidence: 99%